1985
DOI: 10.1002/ijc.2910350505
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cancer studies in the caspian littoral of Iran: Some residual results, including opium use as a risk factor

Abstract: A study was conducted in northern Iran in areas of very high, high and moderately low incidence of oesophageal cancer. Morphine metabolites in urine as an indicator of opium use, and a variety of nutritional and biochemical measures, including salivary antipyrine half-life, were determined in households with a case of oesophageal cancer and in control households. Results on 1,590 individuals showed that the prevalence of appreciable levels (greater than or equal to 1 microgram/ml) of urinary morphine metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
1
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 14 publications
(9 reference statements)
2
42
1
1
Order By: Relevance
“…Factors contributing to this decline may include improved socioeconomic status, more widespread access to piped water, and more fresh fruits and vegetable use due to greater availability of refrigerators. Also, the prevalence of opium use in our study was approximately half of that reported in the 1970s (Ghadirian et al, 1985), when sukhteh use was common (Hewer et al, 1978), but not reported by our subjects.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Factors contributing to this decline may include improved socioeconomic status, more widespread access to piped water, and more fresh fruits and vegetable use due to greater availability of refrigerators. Also, the prevalence of opium use in our study was approximately half of that reported in the 1970s (Ghadirian et al, 1985), when sukhteh use was common (Hewer et al, 1978), but not reported by our subjects.…”
Section: Discussioncontrasting
confidence: 51%
“…An ecologic study in northern Iran found that 50% (20 out of 40) of adults in ESCC high-risk areas, compared with only 11% (10 out of 90) of those in medium-or low-risk areas, tested positive for urine morphine metabolites (Joint Iran-IARC Study Group, 1977). In a subsequent study of 1590 rural individuals, the prevalence of appreciable levels (X1 mg ml À1 ) of urinary morphine metabolites was almost six-fold higher among residents of high-risk vs low-risk areas (Ghadirian et al, 1985). Among the spouses of 41 cases and 41 age-matched controls, there was a two-fold, nonsignificant, increased risk associated with the presence of urinary morphine metabolites.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations